Performance of sealed lead acid battery enhanced by gas separation membrane technology - Ismail, Ahmad Fauzi; Khoo, T. C.; Kusworo, T. D. (2005)
This paper reports the development of an effective method of controlling the evaporation of electrolyte in the newly developed membrane-assisted sealed lead acid battery for the applications in higher temperature conditions such as in an automotive applications, renewable energy sectors and uninterrupted power supply systems. Real time performance evaluation was conducted to determine the effectiveness of the new battery in retaining the electrolyte. Asymmetric polysulfone membrane that functions as an electrolyte retainer was introduced and attached to the battery using a special designed battery top cover assembly. The in-car testing results exhibited that during charging process, electrolyte losses of a membrane-assisted sealed lead acid battery over a period of 1440 hours is approximately 0.134 grams per hour as compared to 1.790 grams per hour for conventional lead acid battery.